Analysis of the Implementation of Bureaucratic Reform in Improving the Work Efficiency of the Secretariat at Dinas PUPR and PERA of East Kalimantan Province - An Nisa Dwi Oktaviani; Iman Surya (Jurnal Kajian dan Penelitian Umum, 2026)
This study aims to analyze the implementation of bureaucratic reform in improving the work efficiency of the Secretariat of Dinas Pekerjaan Umum, Penataan Ruang, and Perumahan Rakyat East Kalimantan Province. The background of this research is grounded in the increasing demand for local government administration that is more effective, efficient, accountable, responsive, and result-oriented, particularly in supporting regional development and the digital transformation of government. This study employed a descriptive qualitative approach with a case study design. Data were collected through document review and literature study of bureaucratic reform regulations, regional apparatus planning documents, government performance data, administrative digitalization reports, and relevant scientific literature. Data analysis was conducted through data condensation, data display, and conclusion drawing and verification. The findings indicate that the implementation of bureaucratic reform within the secretariat needs to be directed toward the restructuring of work procedures, strengthening of accountability, simplification of procedures, proportional division of tasks, and utilization of integrated digital systems. Administrative digitalization plays an important role in accelerating document management, reporting, coordination, archiving, as well as personnel and financial administration. However, work efficiency cannot be achieved merely through the use of applications; it must also be accompanied by changes in business processes, improvement of employee competencies, strengthening of digital literacy, and leadership commitment. Supporting factors for bureaucratic reform include leadership, adaptive work culture, apparatus competence, and work innovation. Meanwhile, inhibiting factors include lengthy procedures, unequal workload distribution, suboptimal coordination, and a rigid administrative culture. This study recommends strengthening performance-based work management, integrating digital systems, simplifying SOPs, and conducting continuous monitoring of secretariat work processes. Thus, the secretariat can serve as a driving force for internal governance that is more orderly, faster, transparent, and capable of supporting the sustainable achievement of technical programs within the regional agency.